2020
DOI: 10.1093/deafed/enaa029
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Cyberbullying among Students with Cochlear Implants

Abstract: Bullying is a significant problem for young people nowadays, regardless of their identity, culture, or background. Although the scientific evidence warns of a greater impact of bullying on vulnerable groups such as cochlear implant (CI) users, few specific studies have been carried out in this regard. As such, the fundamental objective of this study was to estimate the prevalence of both traditional bullying and cyberbullying among Spanish adolescents and young people with CI. Parents with children CI users we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…In this case, dependency on the CI will be experienced as stressful. Feijóo et al (2021) reported increased prevalence rates of peer victimization of young CI users compared to normal-hearing peers. 7 Warner-Czyz et al (2018) found higher rates among young CI users compared to adolescents with hearing aids.…”
Section: Perspective: Cochlear Implant-specific Risks Can Be a Burden...mentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, dependency on the CI will be experienced as stressful. Feijóo et al (2021) reported increased prevalence rates of peer victimization of young CI users compared to normal-hearing peers. 7 Warner-Czyz et al (2018) found higher rates among young CI users compared to adolescents with hearing aids.…”
Section: Perspective: Cochlear Implant-specific Risks Can Be a Burden...mentioning
confidence: 99%
“…In this case, dependency on the CI will be experienced as stressful Feijóo et al (2021). reported increased prevalence rates of peer victimization of young CI users compared to normal-hearing peers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kada je reč o deci i adolescentima sa kohlearnim implantatom, zabeležena rasprostranjenost sajber vršnjačkog nasilja, odnosno sajber viktimizacije iznosi 7%, odnosno 9%, i niža je u odnosu na rasprostranjenost tradicionalnih oblika ove vrste nasilja (Feijóo et al, 2021). Kao moguće objašnjenje ovakvog nalaza, autori su naveli poteškoće u prepoznavanju maltertiranja čak i od strane samih žrtava, što je potvrđeno i u istraživanju kojim su obuhvaćeni adolescenti i odrasle osobe sa ometenošću (González-Calatayud et al, 2021).…”
Section: Faktori Rizika I Korelatiunclassified
“…ili sestrama, što je empirijski prikazano na slučaju dece i adolescenata sa kohlearnim implantatom (Feijóo et al, 2021).…”
Section: Faktori Rizika I Korelatiunclassified